Structural biology of membrane-acting peptides: Conformational plasticity of anticoccidial peptide PW2 probed by solution NMR - Cruzeiro-Silva, C.; Gomes-Neto, F.; Tinoco, L. W.; Cilli, Eduardo Maffud [UNESP]; Barros, P. V. R. [UNESP]; Lapido-Loureiro, P. A. [UNESP]; Bisch, P. M. [UNESP]; Almeida, F. C. L.; Valente, A. P. (Elsevier B.V., 2007)
The bottleneck for the complete understanding of the structure-function relationship of flexible membrane-acting peptides is its dynamics. At the same time, not only the structure but also the dynamics are the key points for their mechanism of action. Our model is PW2, a TRP-rich, cationic peptide selected from phage display libraries that shows anticoccidial activity against Eimeria acervulina. In this manuscript we used a combination of several NMR techniques to tackle these difficulties. The structural features of the membrane-acting peptide PW2 was studied in several membrane mimetic environments: we compared the structural features of PW2 in SDS and DPC micelles, that were reported earlier, with the structure properties in different lipid vesicles and the peptide free in water. We were able to unify the structural information obtained in each of these systems. The structural constraints of the peptide free in water were fundamental for the understanding of plasticity necessary for the membrane interaction. Our data suggested that the WWR sequence is the region responsible for anchoring the peptide to the interfaces, and that this same region displays some degree of conformational order in solution. For PW2, we found that affinity is related to the aromatic region, by anchoring the peptide to the membrane, and specificity is related to the N- and C-termini, which are able to accommodate in the membrane due to its plasticity. (C) 2007 Elsevier B.V. All rights reserved.